Sentralisasi Kebijakan dan Keterbatasan Otonomi Daerah: Desentralisasi Pemerintahan Lokal pada Masa Orde Baru - Angye Mareta Y; Aldri Frinaldi; Hendra Naldi; Lince Magriasti (Faculty of Social Science, Universitas Negeri Padang, 2026)
This study aims to analyze the dynamics of government decentralization in Indonesia before and during the New Order era, as well as its impact on local government. The method used is a literature review, examining various legal sources, policy documents, and relevant academic studies. The data used in this research is entirely derived from secondary data, which is obtained through the examination of existing literature and scientific documents. These data sources include official government documents such as Law No. 5 of 1974 on the Basic Principles of Regional Government, the Outline of State Policy (GBHN), and the Five-Year Development Plan (Repelita) that formed the basis of national policies during the New Order era. In addition, the study also uses academic books discussing decentralization theory, regional government systems, and development policies in Indonesia. Additional data sources are obtained from journal articles, research reports published between 1990 and 2020, focusing on decentralization and centralization in the Indonesian government. The search tools used to find academic literature include Google Scholar, JSTOR, and ScienceDirect. The findings of the study reveal that before the New Order, decentralization was limited due to political instability and weak regional bureaucratic capacity. During the New Order, although legally reinforced through Law No. 5 of 1974 on the Basic Principles of Regional Government, the practice of decentralization was, in fact, illusory, as the central government maintained primary control over policies, budgets, and the appointment of local leaders. Strong centralization did indeed create stability and uniform development, but it also led to disparities between regions, low public participation, and limited local innovation. Therefore, decentralization during the New Order was more administrative than substantive and serves as an important lesson for strengthening regional autonomy in the reform era.